Economic implications of agricultural water use in eastern India - Xenarios, Stefanos; Amarasinghe, Upali A.; Sharma, Bharat R. (Informa UK Limited, 2011)
The irrigation services are often state-subsidized in agrarian economies for the enhancement of agricultural productivity while they also target poverty alleviation. The agriculture-dependent states of India offer representative examples of undervalued irrigation services mainly sourced by canal networks. However, canal irrigation is nowadays lagging behind private groundwater initiatives but with significant costs which question the concept of low water pricing in agriculture. This paper assesses irrigation water costs in representative backward clusters of Bihar state in eastern India while the effects on different landholding groups are analysed. The results indicate that marginal landholders heavily rely on purchased water from unofficial markets while they pay the highest amount for irrigation. This is due to limited access in the canal network, possession of inefficient pumping systems and cultivation of crops with a high demand for water. However, acute policy reforms could drastically decrease water costs and improve agricultural productivity.